Antistatic plastic film and preparation method thereof
By using modified antistatic agents in antistatic plastic films, combined with the characteristics of graphite, palm fiber and sodium alginate, a conductive network and a tight interface structure are formed, which solves the problem of insufficient mechanical properties of traditional antistatic materials and achieves efficient antistatic and mechanical performance improvements.
Patent Information
- Application Number
- CN202411850414.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While improving antistatic properties, traditional antistatic plastic films often reduce mechanical properties, such as toughness, tensile strength and impact resistance, resulting in the impact of reliability and durability in practical applications.
Modified antistatic agent is used, which consists of graphite, palm fiber and sodium alginate. Through the conductive properties of graphite, the strength of palm fiber and the film-forming properties of sodium alginate, a conductive network and a tight interface structure are formed to enhance the antistatic and mechanical properties of the film.
It significantly improves the antistatic properties and mechanical properties of antistatic plastic films, can effectively prevent electrostatic discharge, enhance tensile strength, tear strength and toughness, and improve the overall performance of the film.
Smart Images

Figure BDA0005190427830000081
Abstract
Description
Technical Field
[0001] The present invention relates to the field of plastic films, and more specifically, to an antistatic plastic film and a preparation method thereof. Background Art
[0002] In today's world of rapid technological and social development, product quality has become an indispensable key factor in market competition. Especially in the electronics industry, with the increasing application of precision electronic products, these products have become significantly more sensitive to environmental conditions, especially electrostatic environments. Static electricity problems may not only lead to performance degradation of electronic products, but also cause equipment failure or damage, which in turn has a serious impact on product reliability and service life. Therefore, the development of materials with excellent antistatic properties has become an important research direction in the electronics industry and even in the entire field of packaging and protective materials.
[0003] As a core material in packaging, protection and electronic device manufacturing, the improvement of antistatic properties of plastic film is particularly critical. Traditional antistatic treatment methods include adding conductive fillers, such as carbon black, metal powder, etc. These fillers can effectively improve the conductivity of the material and achieve rapid dissipation of static electricity.
[0004] However, the introduction of conductive fillers also brings problems that cannot be ignored. Too much conductive filler will significantly reduce the toughness, tensile strength and impact resistance of the plastic film, making the film more likely to break or deform when subjected to external forces, thus affecting its reliability and durability in practical applications. Too little conductive filler will make the antistatic ability of the plastic film poor. Summary of the invention
[0005] In order to enhance the antistatic ability of a plastic film and improve its mechanical properties, the present application provides an antistatic plastic film and a preparation method thereof.
[0006] In a first aspect, the present application provides an antistatic plastic film, which adopts the following technical solution: An antistatic plastic film comprises the following raw materials in percentage by mass: 95-105 parts of polypropylene resin, 1-5 parts of pigments and fillers, 1-5 parts of anti-blocking agents, 0.01-1 parts of gloss regulators, and 5-10 parts of modified antistatic agents; The raw materials for preparing the modified antistatic agent include graphite, palm fiber and sodium alginate.
[0007] Graphite, as an excellent conductor, has excellent electron conduction ability; palm fiber, as a natural fiber, has certain strength and toughness; sodium alginate, as a natural polymer, has good water solubility and film-forming properties. Graphite adheres to the surface of palm fiber, and sodium alginate can tightly wrap graphite and palm fiber to prevent graphite from falling off the fiber during processing and use.
[0008] In the modified antistatic agent, sodium alginate not only enhances the bonding force between graphite and palm fiber, but also interacts with polypropylene resin through the functional groups on its molecular chain to form chemical bonds or physical crosslinking points. This bridging effect further enhances the interfacial bonding force between the fiber and the resin matrix, which helps to improve the overall mechanical properties of the film.
[0009] The modified antistatic agent is evenly dispersed in the polypropylene resin and can form a conductive network inside the film. This network can effectively conduct and disperse the static charge accumulated on the surface, thereby reducing the electrostatic potential on the film surface and significantly improving the antistatic performance.
[0010] In addition, when the modified antistatic agent is uniformly introduced into the polypropylene resin, it can strengthen and toughen the film. It can absorb and disperse external forces, reduce the generation and propagation of cracks, and thus improve the mechanical properties of the film such as tensile strength, tear strength and toughness.
[0011] Preferably, the raw materials for preparing the modified antistatic agent include, by weight percentage, 10-20 parts of graphite, 20-40 parts of palm fiber, 1-5 parts of sodium alginate, 50-60 parts of water, and 0.1-0.5 parts of coupling agent.
[0012] Preferably, the raw materials for preparing the modified antistatic agent include, by weight percentage, 12-15 parts of graphite, 30-36 parts of palm fiber, 2-3.5 parts of sodium alginate, 50-60 parts of water, and 0.1-0.5 parts of coupling agent.
[0013] By adopting the above technical solution, the dosage and matching relationship of each raw material is further limited, so that the modified antistatic agent can form a specific structure, and the performance of the film can be more fully improved and enhanced.
[0014] Preferably, the particle size of the graphite is 5-10 μm.
[0015] By adopting the above technical solution, the particle size of graphite is further limited so that it can cooperate well with palm fiber to form a tighter interface structure.
[0016] The graphite particles evenly distributed in the modified antistatic agent can also disperse and conduct static charges more effectively, thereby avoiding electrostatic discharge problems caused by charge accumulation.
[0017] Moreover, the graphite particles with this particle size have a relatively larger specific surface area, and the contact area with the polypropylene resin is correspondingly increased, which is conducive to the charge exchange between the graphite particles and the resin, and further improves the antistatic performance.
[0018] Preferably, the gloss regulator is white mineral oil.
[0019] Preferably, the pigment filler is PE masterbatch.
[0020] In a second aspect, the present application provides a method for preparing an antistatic plastic film, using the following technical solution: A method for preparing an antistatic plastic film comprises the following steps: Step 1: preparing a modified antistatic agent, comprising the following steps: Step 1a: Mix graphite, palm fiber and water, and stir at 1500-2000 r / min for 10-20 min to obtain a mixture; Step 1b: mixing sodium alginate and the stirring object until uniform to obtain a mixture; Step 1c: diluting the coupling agent with an alcohol solution to obtain a coupling agent solution; mixing the coupling agent solution with the mixture to obtain a modified product; Step 1d: drying the modified product to obtain a modified antistatic agent; Step 2: Mix the raw materials and keep them at 200-220°C for 1.5-2h; Step 3: Extrude the material of step 2, and then blow mold it to obtain an antistatic plastic film.
[0021] By adopting the above technical solution, when preparing the modified antistatic agent, the graphite is firstly adhered to the palm fiber under high-speed stirring, and then the graphite is wrapped with sodium alginate, so that the three form a special tightly matched whole. Then the coupling agent is used to modify the whole, giving it good compatibility in the polypropylene resin, making it easier to achieve uniform distribution and tight combination, thereby further exerting the effect of the modified antistatic agent and improving the antistatic and mechanical properties of the film.
[0022] Preferably, the palm fiber is soaked in a 5-10% alkali solution for 2-3 hours, taken out and dried to obtain alkali-soaked palm fiber; the alkali-soaked palm fiber is then mixed with graphite and water to obtain a stirrer.
[0023] By adopting the above technical scheme, the palm fiber is treated with an alkaline solution, and the surface of the obtained alkali-soaked palm fiber is rougher, which facilitates the subsequent graphite to adhere more firmly to the surface of the alkali-soaked palm fiber, effectively enhancing the performance improvement effect of the modified antistatic agent on the film.
[0024] Preferably, in step 1c, the mass ratio of the coupling agent to the alcohol solution is 1:(3-5).
[0025] In summary, this application has the following beneficial effects: 1. The antistatic plastic film provided by the present application significantly improves the antistatic performance of the film by introducing a special modified antistatic agent. The modified antistatic agent utilizes the excellent electron conduction ability of graphite, combines the natural strength of palm fiber and the film-forming property of sodium alginate, and forms an efficient conductive network. This network can quickly conduct and disperse the static charge accumulated on the surface, significantly reduce the electrostatic potential on the surface of the film, and thus effectively prevent the occurrence of electrostatic discharge.
[0026] 2. The modified antistatic agent composed of graphite, palm fiber and sodium alginate plays a significant role in strengthening and toughening the film. The modified antistatic agent effectively improves the mechanical properties of the film through its unique structural characteristics. As an excellent conductor, graphite not only enhances the antistatic ability of the film, but its hard particles can also form physical support points inside the palm fiber. The natural strength and toughness of palm fiber provide good mechanical support, allowing the film to better absorb and disperse stress when subjected to external forces. The mechanical properties of the film are improved from many aspects. DETAILED DESCRIPTION
[0027] The present application is further described in detail below in conjunction with embodiments.
[0028] The raw materials used in the following examples and comparative examples are all commercially available products. Example
[0029] Example 1 An antistatic plastic film comprises the following raw materials: polypropylene resin, pigments and fillers, anti-blocking agents, gloss regulators and modified antistatic agents.
[0030] The specific amount of each raw material is shown in Table 1.
[0031] The polypropylene resin is commercially available, specifically Hengli Petrochemical, L5E89.
[0032] The pigment and filler were PE masterbatch purchased from Dongguan Jincai New Materials Co., Ltd.
[0033] The antiblocking agent is commercially available from Dongguan Donglai Plastic Co., Ltd., GE-2.
[0034] The gloss regulator was white mineral oil purchased from Shaoguan Runbo Trading Co., Ltd.
[0035] The raw materials for preparing the modified antistatic agent include graphite, palm fiber, sodium alginate, water and coupling agent.
[0036] The particle size of graphite is 5-10 μm.
[0037] The coupling agent is KH-560.
[0038] The specific dosage of raw materials for the preparation of modified antistatic agent is shown in Table 2.
[0039] This embodiment also provides a method for preparing an antistatic plastic film, comprising the following steps: Step 1: preparing a modified antistatic agent, comprising the following steps: Step 1a: The mass ratio of palm fiber to 8% sodium hydroxide solution is 1:5. The palm fiber is soaked in 8% sodium hydroxide solution for 2.5 hours.
[0040] The solid and liquid are separated, and the solid part is dried by hot air to a constant weight to obtain alkali palm fiber.
[0041] Step 1b: Put graphite and alkali foam palm fiber into water, mix, and stir at 1800 r / min for 15 minutes to obtain a stirrer.
[0042] Step 1c: Add sodium alginate into the stirred substance, stir and mix until uniform, to obtain a mixture.
[0043] Step 1d: dilute the coupling agent with an ethanol solution, wherein the mass ratio of the coupling agent to the ethanol solution is 1:4 to obtain a coupling agent solution.
[0044] The coupling agent solution was added into the mixture, stirred and mixed, and allowed to stand and soak for 60 minutes to obtain a modified product.
[0045] Step 1e: drying the modified product with hot air at 80° C. to obtain a modified antistatic agent.
[0046] Step 2: Put all the raw materials into the mixing tank, start stirring at 800r / min, and stir for 5 minutes.
[0047] Step 3: Keep the material in step 2 at 210°C for 1.5h.
[0048] Step 4: Extrude the material of step 3, and then blow mold it to obtain an antistatic plastic film.
[0049] Example 2 An antistatic plastic film, which is different from Example 1 in that the specific amounts of various raw materials in the antistatic plastic film are shown in Table 1.
[0050] The specific dosage of raw materials for the preparation of modified antistatic agent is shown in Table 2.
[0051] A method for preparing an antistatic plastic film, which is different from Example 1 in that some parameters are different, specifically comprises the following steps: Step 1: preparing a modified antistatic agent, comprising the following steps: Step 1a: The mass ratio of palm fiber to 5% sodium hydroxide solution is 1:5. The palm fiber is soaked in 5% sodium hydroxide solution for 3 hours.
[0052] The solid and liquid are separated, and the solid part is dried by hot air to a constant weight to obtain alkali palm fiber.
[0053] Step 1b: Put graphite and alkali foam palm fiber into water, mix them, and stir them at 1500 r / min for 20 minutes to obtain a stirrer.
[0054] Step 1c: Add sodium alginate into the stirred substance, stir and mix until uniform, to obtain a mixture.
[0055] Step 1d: dilute the coupling agent with an ethanol solution, wherein the mass ratio of the coupling agent to the ethanol solution is 1:3 to obtain a coupling agent solution.
[0056] The coupling agent solution was added into the mixture, stirred and mixed, and allowed to stand and soak for 60 minutes to obtain a modified product.
[0057] Step 1e: drying the modified product with hot air at 80° C. to obtain a modified antistatic agent.
[0058] Step 2: Put all the raw materials into the mixing tank, start stirring at 800r / min, and stir for 5 minutes.
[0059] Step 3: Keep the material in step 2 at 220°C for 1.5h.
[0060] Step 4: Extrude the material of step 3, and then blow mold it to obtain an antistatic plastic film.
[0061] Example 3 An antistatic plastic film, which is different from Example 1 in that the specific amounts of various raw materials in the antistatic plastic film are shown in Table 1.
[0062] The specific dosage of raw materials for the preparation of modified antistatic agent is shown in Table 2.
[0063] A method for preparing an antistatic plastic film, which is different from Example 1 in that some parameters are different, specifically comprises the following steps: Step 1: preparing a modified antistatic agent, comprising the following steps: Step 1a: The mass ratio of palm fiber to 10% sodium hydroxide solution is 1:5. The palm fiber is soaked in 10% sodium hydroxide solution for 2 hours.
[0064] The solid and liquid are separated, and the solid part is dried by hot air to a constant weight to obtain alkali palm fiber.
[0065] Step 1b: Put graphite and alkali foam palm fiber into water, mix them, and stir them at 2000 r / min for 10 minutes to obtain a stirrer.
[0066] Step 1c: Add sodium alginate into the stirred substance, stir and mix until uniform, to obtain a mixture.
[0067] Step 1d: dilute the coupling agent with an ethanol solution, wherein the mass ratio of the coupling agent to the ethanol solution is 1:5 to obtain a coupling agent solution.
[0068] The coupling agent solution was added into the mixture, stirred and mixed, and allowed to stand and soak for 60 minutes to obtain a modified product.
[0069] Step 1e: drying the modified product with hot air at 80° C. to obtain a modified antistatic agent.
[0070] Step 2: Put all the raw materials into the mixing tank, start stirring at 800r / min, and stir for 5 minutes.
[0071] Step 3: Keep the material in step 2 at 200°C for 2h.
[0072] Step 4: Extrude the material of step 3, and then blow mold it to obtain an antistatic plastic film.
[0073] Table 1 raw material Example 1 Example 2 Example 3 Polypropylene resin (kg) 100 95 105 Pigment and filler (kg) 4 1 5 Opening agent (kg) 2 1 5 Gloss regulator (kg) 0.1 0.01 1 Modified antistatic agent (kg) 8 5 10 Example 4 An antistatic plastic film, which is different from Example 1 in that the specific amounts of raw materials used in preparing the modified antistatic agent are shown in Table 2.
[0074] Table 2 raw material Example 1 Example 2 Example 3 Example 4 Graphite(kg) 12 10 20 15 Palm fiber(kg) 30 20 40 36 Sodium alginate(kg) 2 1 5 3.5 Water (kg) 55 50 60 55 Coupling agent(kg) 0.3 0.1 0.5 0.3 Example 5 A method for preparing an antistatic plastic film, which is different from that of Example 1 in that the alkali soaking treatment of palm fiber is omitted.
[0075] The specific steps include: Step 1: preparing a modified antistatic agent, comprising the following steps: Step 1a: Graphite and palm fiber are added into water, mixed, and stirred at 1800 r / min for 15 min to obtain a stirred product.
[0076] Step 1b: Add sodium alginate into the stirred substance, stir and mix until uniform, to obtain a mixture.
[0077] Step 1c: dilute the coupling agent with an ethanol solution, wherein the mass ratio of the coupling agent to the ethanol solution is 1:4 to obtain a coupling agent solution.
[0078] The coupling agent solution was added into the mixture, stirred and mixed, and allowed to stand and soak for 60 minutes to obtain a modified product.
[0079] Step 1d: drying the modified product with hot air at 80° C. to obtain a modified antistatic agent.
[0080] Step 2: Put all the raw materials into the mixing tank, start stirring at 800r / min, and stir for 5 minutes.
[0081] Step 3: Keep the material in step 2 at 210°C for 1.5h.
[0082] Step 4: Extrude the material of step 3, and then blow mold it to obtain an antistatic plastic film.
[0083] Comparative Example Comparative Example 1 An antistatic plastic film, which is different from Example 1 in that palm fiber is replaced by sisal fiber.
[0084] Comparative Example 2 An antistatic plastic film, which is different from Example 1 in that sodium alginate is replaced by xanthan gum.
[0085] Comparative Example 3 An antistatic plastic film, which is different from Example 1 in that sodium alginate is omitted.
[0086] A method for preparing an antistatic plastic film, which is different from Example 1 in that the preparation method of the modified antistatic agent is different, specifically comprising the following steps: Step 1a: The mass ratio of palm fiber to 8% sodium hydroxide solution is 1:5. The palm fiber is soaked in 8% sodium hydroxide solution for 2.5 hours.
[0087] The solid and liquid are separated, and the solid part is dried by hot air to a constant weight to obtain alkali palm fiber.
[0088] Step 1b: Put graphite and alkali foam palm fiber into water, mix, and stir at 1800 r / min for 15 minutes to obtain a stirrer.
[0089] Step 1c: dilute the coupling agent with an ethanol solution, wherein the mass ratio of the coupling agent to the ethanol solution is 1:4 to obtain a coupling agent solution.
[0090] The coupling agent solution was added into the mixture, stirred and mixed, and allowed to stand and soak for 60 minutes to obtain a modified product.
[0091] Step 1d: drying the modified product with hot air at 80° C. to obtain a modified antistatic agent.
[0092] Comparative Example 4 An antistatic plastic film, which is different from Example 1 in that the raw materials for preparing the modified antistatic agent include 30 kg of graphite and 12 kg of palm fiber.
[0093] Performance testing 1. Antistatic effect: The surface resistance of the antistatic plastic films of Examples 1-5 and Comparative Examples 1-4 was tested with reference to GB / T 1410-2006 "Test Method for Volume Resistivity and Surface Resistivity of Solid Insulating Materials". The surface resistance is recorded in Table 3.
[0094] 2. Tensile strength: The tensile strength of the antistatic plastic films of Examples 1-5 and Comparative Examples 1-4 was tested with reference to GB / T 1040 "Test for tensile properties of plastics". The tensile strength is recorded in Table 3.
[0095] 3. Izod impact strength: The Izod impact strength of the antistatic plastic films of Examples 1-5 and Comparative Examples 1-4 was tested with reference to GB / T 1843 "Determination of Izod impact strength of plastics". The Izod impact strength is recorded in Table 3.
[0096] Table 3 Comparative Example 1-2 is an antistatic plastic film obtained by replacing palm fiber and sodium alginate with other raw materials on the basis of Example 1. According to the test data in Table 3, the surface resistivity of Comparative Example 1-2 is greater than that of Example 1, and the tensile strength and cantilever beam impact strength are smaller than those of Example 1. It is shown that the antistatic effect of Example 1 is better than that of Comparative Example 1-2, and the mechanical strength is also better. In other words, after destroying the combination of palm fiber, sodium alginate and graphite, the antistatic and mechanical properties of the antistatic plastic film cannot be effectively improved.
[0097] Comparative Example 3 is based on Example 1, but sodium alginate is omitted, so that graphite cannot be firmly attached to palm fiber, and the special structure of the modified antistatic agent cannot be generated, so that the antistatic effect is not as good as that of Example 1; the loss of graphite as support inside the palm fiber also significantly reduces the tensile strength. Comparative Example 4 is based on Example 1, but the amount of graphite and palm fiber is changed, breaking the adhesion relationship between graphite and palm fiber, so that the performance is reduced.
[0098] In addition, according to the test data in Table 3, Example 1 has higher mechanical properties and antistatic properties than Example 5. This indicates that the alkali bubble treatment of palm fiber can make its surface rougher, effectively enhance the coordination relationship between the palm fiber and graphite and sodium alginate, thereby significantly improving the performance.
[0099] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An antistatic plastic film, characterized in that: In terms of mass percentage, it includes the following raw materials: 95-105 parts of polypropylene resin, 1-5 parts of pigments and fillers, 1-5 parts of anti-blocking agents, 0.01-1 parts of gloss regulators, and 5-10 parts of modified antistatic agents; The raw materials for preparing the modified antistatic agent include graphite, palm fiber and sodium alginate.
2. The antistatic plastic film according to claim 1, characterized in that: The raw materials for preparing the modified antistatic agent include, by weight percentage, 10-20 parts of graphite, 20-40 parts of palm fiber, 1-5 parts of sodium alginate, 50-60 parts of water, and 0.1-0.5 parts of coupling agent.
3. The antistatic plastic film according to claim 2, characterized in that: The raw materials for preparing the modified antistatic agent include, by weight percentage, 12-15 parts of graphite, 30-36 parts of palm fiber, 2-3.5 parts of sodium alginate, 50-60 parts of water, and 0.1-0.5 parts of coupling agent.
4. The antistatic plastic film according to claim 1, characterized in that: The particle size of the graphite is 5-10 μm.
5. The antistatic plastic film according to claim 1, characterized in that: The gloss regulator is white mineral oil.
6. The antistatic plastic film according to claim 1, characterized in that: The pigment and filler are PE masterbatches.
7. A method for preparing an antistatic plastic film, based on the antistatic plastic film according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: preparing a modified antistatic agent, comprising the following steps: Step 1a: Mix graphite, palm fiber and water, and stir at 1500-2000 r / min for 10-20 min to obtain a mixture; Step 1b: mixing sodium alginate and the stirring object until uniform to obtain a mixture; Step 1c: diluting the coupling agent with an alcohol solution to obtain a coupling agent solution; mixing the coupling agent solution with the mixture to obtain a modified product; Step 1d: drying the modified product to obtain a modified antistatic agent; Step 2: Mix the raw materials and keep them at 200-220°C for 1.5-2h; Step 3: Extrude the material of step 2, and then blow mold it to obtain an antistatic plastic film.
8. The method for preparing the antistatic plastic film according to claim 7, characterized in that: The palm fiber is soaked in a 5-10% alkali solution for 2-3 hours, taken out and dried to obtain alkali-soaked palm fiber; the alkali-soaked palm fiber is then mixed with graphite and water to obtain a stirrer.
9. The method for preparing the antistatic plastic film according to claim 7, characterized in that: In the step 1c, the mass ratio of the coupling agent to the alcohol solution is 1:(3-5).
Citation Information
Patent Citations
Flame-retarding anti-static polypropylene fiber and preparation method thereof
CN110565196A
Antistatic functional fiber material as well as preparation method and application thereof
CN116397349A
Antistatic modified polypropylene material and preparation method thereof
CN117247631A
Antistatic biaxially oriented polypropylene composition and its preparation method
CN1966561A
Antistatic thermoplastic resin composition
KR1020100056922A